Exploring stevioside binding affinity with various proteins and receptors actively involved in the signaling pathway and a future candidate for diabetic patients - Khan, Salman; Ahmad, Nisar; Fazal, Hina; Saleh, Ibrahim A.; Abdel-Maksoud, Mostafa A.; Malik, Abdul; AbdElgayed, Gehad; Jalal, Arshad; Rauf, Kamran; Ali, Liaqat; Ullah, Sami; Niqabullah,; et al. (Frontiers in Pharmacology, 2024)
Diabetes is a chronic metabolic disease characterized by elevated blood glucose levels and is one of the main global health concerns. Synthetic sugar substrate has many side effects such as leukemia, bladder cancer, hepatotoxicity, breast cancer, headache, and brain toxicity. The WHO and FDA has recently banned some of the synthetic sugar alternatives due to their carcinogenic effects. Therefore, the main objective of the current study was to investigate the safety and binding affinity of Stevioside with Glucose Transpoter-4 (GLUT-4), Akt, Insulin Receptor (IR) and InsulinReceptor Substrate-1 (IRS-1) to confirmed that Stevioside is one the potent natural sweetener/drug for diabetes. This study delves into the molecular interaction between Stevioside and key diabetic proteins: GLUT-4, Akt, IR and IRS-1. A precise molecular docking approach was used to simulate the binding affinity of Stevioside to these proteins. Computer-aided design and drafting/drug designing (CADD) play a key role in the identification of and proper presentation of different graphical and structural form of drugs and its attachment sites. The pharmacokinetic properties of the molecule should be taken into consideration as important variables throughout the virtual screening process. The result of active site analysis of GLUT-4, Akt, IR and IRS-1 showed a zone